Human factors awareness and recognition during multidisciplinary team meetings. (9th April 2019) - Oeppen, Rachel S.; Davidson, Mike; Scrimgeour, Duncan S.; Rahimi, Siavash; Brennan, Peter A.
Abstract: Multidisciplinary team (MDT) meetings are widely used throughout medicine and dentistry, bringing together expertise and different opinions across many disciplines to benefit patient care. Depending on the cancer site and specialties involved, some MDTs can last for several hours, especially if there are many complex patients to discuss. However, concentration and attention can vary and distraction is almost inevitable with separate conversations between MDT members and the ever‐increasing use of smartphones. The role of human factors (HF) in contributing to error is well known in high‐risk activities including medicine and surgery. Surprisingly, while there is increasing awareness of their importance by medical and dental professionals to enhance patient safety, to our knowledge nothing to date has been published about the possible effect and role of HF at MDTs. Here we provide a brief HF overview and focus on the factors at an MDT that could lead to distraction, providing suggestions (including some from aviation) for possible ways to enhance and improve discussion during these often‐long meetings. It is hoped that this paper will generate some thought and discussion around the current "normal" MDT practice in head and neck and other specialties and challenge colleagues to embrace HF and safety principles in a just and learning culture.